Spiritual Management in Islamic Education Management Studies (MPI) in the Covid-19 Era - Wati, Lilis (Proceeding International Conference on Religion, Science and Education, 2022)
The COVID-19 pandemic is a disease outbreak that has brought enormous changes to the world today. Starting from the end of 2019 until now. In the early days of Covid-19, there was a massive lockdown, which caused us to feel very drastic changes, including in the world of education. The purpose of this study is to describe the Concept of Spiritual Management in the study of Islamic education management in the Covid-19 era. This research uses a qualitative research approach through a literature study approach. Namely collecting data, data analysis, data reduction, and data verification. Based on the results of the study, it shows that the principal carries out his role well as a manager relying on religious thinking, to build himself, and strengthen institutions, the principal also carries out the basics, management in general. Spiritual management is very influential in an institution to deal with the changing world today in the era of covid-19.